Pengaruh Penilaian Tingkat Kesehatan Bank Metode RGEC terhadap Penyaluran Pembiayaan di BTPN Syariah - Safira, Shafa; Yetty, Fitri (Islamic Economics and Business Review, 2023)
The amount of financing disbursed by banks might vary depending on a number of internal and external factors. Therefore, banks must pay attention to evaluating a bank's soundness in its operational activities as a kind of supervision to ensure that the company's existence continues to run smoothly and that the distribution of finance may be optimally distributed. The assessment of bank health in this study is by POJK No.8/POJK.03/2014 using the risk approach (RGEC) as measured by financial ratios only with NPF (Risk Profile), ROA (Earning), and CAR (Capital) variables. PT BTPN Syariah's annual report for 2014–2021 was used as a research sample. With secondary data collection methods using multiple linear analyses and SPSS software for data analysis. The results of the study show that NPF, ROA, and CAR partially positively have no significant effect but simultaneously have a significant effect on financing disbursement at BTPN Syariah.